THE NIETZSCHEAN CULTURAL POLICY AND THE EUROPE OF THE FUTURE: STUDIES BEYOND GOOD AND EVIL - das Chagas Lacerda, Oclécio (Seven Editora, 2025)
In Beyond Good and Evil, Nietzsche takes on the task of preparing the way for the advent of a higher kind of culture for Europe. This requires a genealogical work, which leads to the origins of this new culture, access to which is very rare, for it’s an opposite kind of widespread cultural weakness across the European continent. The identification of such sources requires a different view on modern Europe, which takes into account the psychology and physiology. From this new investigative approach you can run the cultivation work of certain rare cultural elements, almost extinct and difficult to proliferate and that still have an underground life, even in regions where the predominant culture proliferates most in Europe. Nietzsche refers in particular to France, the cradle of weak and degenerate culture, but prevalent because its fundamental values of Christian compassion and democratic equality. DOI: https://doi.org/10.56238/sevened2025.029-046